A New Model for the Full Inclusion of Precipitation Reactions in the General Ionic Equilibrium Framework of Homogeneous Solutions Based on the Fraction of Species Concept in Heterogeneous Systems - Miguel, Eduardo Rodríguez de San (Journal of Applied Solution Chemistry and Modeling, 2018)
This study aims at extending the general methodology for the study of predominance and reactivity of ionic homogeneous solutions to precipitation reactions. This extension was satisfactorily formulated by the definition of the fraction of species concept in heterogeneous systems for the first time. An easy form to fully integrate the ion product concept with other descriptions of homogeneous ionic reactions, to obtain predominance zone diagrams (PDZ), to enrich the use logarithmic relative diagrams, to generate continuous equations from titration curves, and to generalize side-reaction coefficients to heterogeneous systems using easy-to-compute algorithms of calculation is shown. The new representation was applied in a study case exemplified by the hydrolysis of copper (II) in the absence and the presence of complexing ligands considering soluble and insoluble species of the metal ion. The results perfectly compare to those obtained by established numerical and graphical methods of analysis of solution equilibria showing the equivalence among the different descriptions. Pre-nucleation clusters (PNCs) theory of precipitation reactions was used as a mean to interpret the theoretical implication that this view engendered.